2009
DOI: 10.1007/s10433-009-0134-8
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness among older Europeans

Abstract: More than two decades of research has consistently indicated that feelings of loneliness among older people are more common in southern Europe than in its northern parts, with the lowest rates in Denmark and Sweden. Our analyses based on analysis of 2004-2006 data from 8,787 individuals aged 65 years or older in the SHARE project replicate, update, and extend these findings. We found, similar to previous studies, that the prevalence of feelings of loneliness was more common in the Mediterranean countries than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
175
2
23

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(221 citation statements)
references
References 13 publications
21
175
2
23
Order By: Relevance
“…In the next decade, this situation will change (especially for women): The proportion of widowed older people will become smaller, and the proportions of both married and divorced persons will increase (Kalogirou and Murphy 2006). Living together with a partner is quite often associated with lower prevalence of loneliness (Sundström et al 2009). …”
Section: Cultural Norms As Reference System For Individual Expectationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the next decade, this situation will change (especially for women): The proportion of widowed older people will become smaller, and the proportions of both married and divorced persons will increase (Kalogirou and Murphy 2006). Living together with a partner is quite often associated with lower prevalence of loneliness (Sundström et al 2009). …”
Section: Cultural Norms As Reference System For Individual Expectationsmentioning
confidence: 99%
“…We hope that our tentative theoretical model might help to stimulate further empirical research and open possibilities to broaden the model to other regions of Europe. Comparing Northern and Southern European countries, Sundström and colleagues find that the prevalence of loneliness is higher in the Mediterranean countries than in Northern Europe (Sundström et al 2009)-and point out that this is a puzzling finding because 'this is at variance with our most simplified and cherished views of ''Anomie'' in Nordic countries and ''Gemeinschaft'' in Southern societies'. We believe that our model might be useful in this context.…”
Section: Outlook: Changing Lives In Changing Societiesmentioning
confidence: 99%
“…Previous studies based on SHARE have also shown that elderly old people in the Scandinavian countries are more satisfied with their social network despite less frequent contact [9,10], and report less loneliness despite a higher prevalence of living alone and other indicators of assumed social community [11]. One explanation could be that in the universal welfare regime the family may have a complementary and more positive role in addition to the more daily-based support from public providers.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-national comparisons reveal closer intergenerational contacts in Southern and Eastern Europe, with a family-based welfare model, compared to the Scandinavian universal welfare regime [9]. Even though intergenerational contacts are less frequent in the Scandinavian countries and more old people live alone, several studies report greater satisfaction with the social network as compared to countries in Southern and Eastern Europe [10,11]. Previous studies have also shown that the impact of intergenerational contacts varies across socioeconomic groups and that, for instance, family ties are denser among the less educated and partly compensate for a lack of other resources, even in countries with strong public welfare institutions [12].…”
Section: Introductionmentioning
confidence: 99%
“…While we do not have the space here to offer a full formal analysis of the trends, we can note that three of the six most frequently cited EJA articles that are listed in Thomson ISI's Web of Science deal with loneliness (Dykstra 2009;Scharf and Gierveld 2008;Sundstrom et al 2009). The interpersonal milieu in late life is a domain that is already well covered among the publications that appear in the European Journal of Ageing and we look forward to continued inquiry in this crucial area.…”
mentioning
confidence: 99%